1981
DOI: 10.1104/pp.68.3.673
|View full text |Cite
|
Sign up to set email alerts
|

Ion Distribution in Roots of Barley Seedlings Measured by Electron Probe X-Ray Microanalysis

Abstract: The distribution of ions, particularly K and Na, was studied in roots of barley seedlings grown on various ionic solutions. Analyses were made by means of electron probe x-ray microanalysis using frozen, fractured bulk specimens. By this technique, it was demonstrated that there can be variability in the ratio K/Na measured in the vacuoles of cortical cells, with this ratio often being lower in epidermal cells of the root than in the inner cortex. A sharp difference in the K/Na ratio was also found between cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 5 publications
2
36
0
Order By: Relevance
“…This volume is a function of the electron beam accelerating voltage, the average atomic number of the elements in the sample, and the atomic number of the element analyzed. At an accelerating voltage of 10 kV, the excitation volume in frozen hydrated tissue for Na+ and K+ (as well as other elements of similar atomic number) has been estimated to be 2 to 3 ,um in diameter (18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This volume is a function of the electron beam accelerating voltage, the average atomic number of the elements in the sample, and the atomic number of the element analyzed. At an accelerating voltage of 10 kV, the excitation volume in frozen hydrated tissue for Na+ and K+ (as well as other elements of similar atomic number) has been estimated to be 2 to 3 ,um in diameter (18).…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is possible that in some instances the excited volume for Na extended into the vacuole resulting in a larger xray signal and the perception of greater Na contents in the cytoplasm. Since the excited volume for Cl would be smaller than for Na (18), cytoplasmic Cl content should be resolved more accurately than the Na content. However, if this had been the case, it is likely that problems with excited volume overlap would have resulted in much greater variability from analysis to analysis than was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple mechanisms, including morphological and biochemical adaptations, are probably involved in maintaining this low cytoplasmic Na+/K+ ratio. In barley (Hordeum vulgare), two such mechanisms are extrusion of Na+ into the vacuole across the tonoplast membrane and extrusion of Na+ into the external medium across the plasma membrane (13,16). The energy for Na+ extrusion could be provided by the proton gradients generated by the plasma membrane or tonoplast H+-ATPases.…”
mentioning
confidence: 99%
“…A high external salt concentration is detrimental to many plants due to (1) a decrease of the external water potential, and (2) the accumulation of Na and Cl in the plant cytoplasm, which can cause an inhibition of metabolic processes. Pitman et al (1981) found high concentrations of Na in the vacuole after salt stress and suggested that sequestration of Na into plant vacuoles prevents a toxic accumulation of this element in the cytosol. In salt tolerant wild-turf roots an increase in inorganic phosphate in vacuoles after salt stress has also been observed (Takagishi et al, 1991).…”
Section: mentioning
confidence: 99%